Russia's foreign trade and the economic reforms - Klaus Werner (Intereconomics, 1993)
The Russian Federation now faces a totally new beginning as regards the shaping of its foreign trade relations. The demands made upon its external economic policy by the changes in the political and economic systems on the one hand and the collapse of the formerly unified economic zone of the Soviet Union on the other are so great that, in many respects, consistent answers have yet to be found. To what extent has the Russian government so far succeeded in developing a new foreign trade regime?
Keywords: 330